2010
DOI: 10.1590/s1679-78252010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Resonance characteristics of two-span continuous beam under moving high speed trains

Abstract: The resonance characteristics of a two-span continuous beam traversed by moving high speed trains at a constant velocity is investigated, in which the continuous beam has uniform span length. Each span of the continuous beam is modeled as a Bernoulli-Euler beam and the moving trains are represented as a series of two degrees-of-freedom mass-springdamper systems at the axle locations. A method of modal analysis is proposed in this paper to investigate the vibration of two-span continuous beam. The effects of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…It was well known that if the acceleration response, rather than the displacement response, of a structure is of concern, the contribution of higher modes has to be included in computation [28]. From the convergent verification of computed results of a beam structure under moving train loads in references [29,30], the first 20 modes of shape functions in Eqs. (26) are sufficient to compute the acceleration response of a simple beam.…”
Section: Rail Irregularity (M)mentioning
confidence: 99%
“…It was well known that if the acceleration response, rather than the displacement response, of a structure is of concern, the contribution of higher modes has to be included in computation [28]. From the convergent verification of computed results of a beam structure under moving train loads in references [29,30], the first 20 modes of shape functions in Eqs. (26) are sufficient to compute the acceleration response of a simple beam.…”
Section: Rail Irregularity (M)mentioning
confidence: 99%
“…A considerable amount of research has been conducted on the dynamic responses of railway bridge/track structures subjected to a moving train (Sun and Dhanasekar, 2002;Liu et al, 2009;Lu et al, 2009;Wang et al, 2010;Kim, 2011;Zakeri et al, 2014;Lei and Wang, 2014;Xu et al, 2015). Such research has been conducted particularly in the past three decades and mostly in relation to the rapid development of high-speed railways worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Wang et al (2010) simulated a two-span continuous beam and obtained the two critical velocities causing the resonance response. By means of numerical models, Lu et al (2013) studied the influence of the bridge-to-carriage length ratio and Yang & Lin (2005) demonstrated that the primary frequencies in the bridge response might be caused by the driving frequencies, which are related to the time the train spent crossing the bridge, and the dominant frequencies, caused by the repeated loads.…”
Section: Introductionmentioning
confidence: 99%